The qualitative study of intentional self-harm in Thailand: Focusing on predisposing child-rearing environments and self-harm cessation - Limsuwan, Nida; Lantomrattana, Anyamanee; Prachason, Thanavadee; Tantrarungroj, Thanita; Lorterapong, Passaporn; Thongpan, Masatha; Waleeprakhon, Punjaporn (Frontiers in Psychology, 2023)
Introduction Intentional self-harm in adolescents and young people, including both suicidal behaviors and non-suicidal self-injury (NSSI), is a serious issue in mental health systems. However, the majority of studies on self-harm in adolescents and young people focused on a quantitative methodology which might have limitations in explaining this complex phenomenon of intentional self-harm. Therefore, this study aimed to describe the subjective experiences of adolescents and young people who presented with intentional self-harm in order to provide a better understanding of this behavioral phenomenon. Methods This is an exploratory qualitative study that uses phenomenological processes and thematic analysis. Twenty subjects aged 13–29 years were included in this study. Results The results revealed six themes regarding predisposing child-rearing environments and nine themes regarding factors related to the cessation of intentional self-harm. Moreover, it demonstrated the important functions of self-harm as an intrapersonal strategy for emotional regulation. Discussion In conclusion, this study underscored the importance of understanding the developmental and cessation pathways of these complex behaviors.